New findings on the pharmacodynamic actions of olive oil: our contribution to better evidence about its remedial properties - Duborija-Kovacevic, Natasa; Shavrina, Ksenia (Progress in Nutrition, 2018)
Objective: Olive oil (OO) is a typical Mediterranean product which influences positively the human health, that has been well-recognized since ancient times. Numerous substances isolated from OO, in particular from extra virgin olive oil (EVOO), are still the subjects of extensive scientific researches. The objective of this review was to bring together rather scattered information on the remedial constituents of OO, as well as available data on their pharmacodynamic actions. Material and Methods: For this analysis, we searched for studies on the remedial substances of OO published in English on the PubMed in 2005-2015, in which the pharmacodynamic actions of OO were investigated. We considered studies which were conducted on cell lines and experimental animals, as well as clinical trials. We excluded studies where pharmacodynamic actions of the mentioned substances could not be precisely distinguished and described. Results: Oleic acid decreases the concentration and oxidation of LDL, reduces the risk of developing cardiovascular diseases, as well as possesses some anti-tumor activities. Oleuropein exhibits neuro-, hepato- and cardioprotective activities, possesses hypotensive and anti-inflammatory effects, as well as strong potential in prevention of colon and breast cancer. Hydroxytyrosol possesses pronounced anti-oxidant properties, as well as anti-inflammatory, anti-platelet and anti-tumor activities. Tyrosol exhibits anti-oxidant properties that are less pronounced than those of hydroxytyrosol. Conclusion: OO has multiple beneficial effects of protecting the humans’ health and even of preventing and/or treating different diseases. Additional measures should be taken to encourage the production and consumption of OO globally, as well as to inform and educate the professional and general public about its favorable pharmacodynamic actions on human health.